Dans la jungle de l’intime : enquête lexicographique et lexicométrique (1606-2008) - Véronique Montémont (Itinéraires)
Since it first appeared in the French dictionaries of the seventeenth century, the acceptance of the term intime has diversified and proliferated: as a qualifier reserved for a relationship of affection or friendship, it was then used in a number of fields (theology, the natural sciences, psychology) and finally achieved the status of substantive at the end of the twentieth century. The analysis of its lexicographie evolution has been compared here to its uses in language in the literary texts and the titles of works published in France between 1600 and 2009. The interpretation of its co-occurrents led to the appearance of a trend of the same name at the end of nineteenth century, and to the application of the term to various objects, which, paradoxically, introduced the notion of intimate into the public sphere today.